2014
DOI: 10.1095/biolreprod.114.122945
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CCCTC-Binding Factor (CTCF) in Genomic Imprinting, Development, and Reproduction1

Abstract: CCCTC-binding factor (CTCF) is the major protein involved in insulator activity in vertebrates, with widespread DNA binding sites in the genome. CTCF participates in many processes related to global chromatin organization and remodeling, contributing to the repression or activation of gene transcription. It is also involved in epigenetic reprogramming and is essential during gametogenesis and embryo development. Abnormal DNA methylation patterns at CTCF motifs may impair CTCF binding to DNA, and are related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 138 publications
2
33
0
Order By: Relevance
“…In bull spermatozoa, a study by Hur et al [68] reported that the protein of KCK4 localizes to the equatorial region of acrosome reacted sperm, and that inhibitor of the K 2P channels reduces not only fertilization but also development of bovine and mouse embryos in vitro. Interestingly, a DMR was located in the CTCF gene, which has been associated with spermatogenesis and male fertility [70, 71]. The CTCF gene plays a critical role in genome-wide gene regulation and has roles in epigenetic reprogramming, gametogenesis and embryo development and is also associated with fertility, as reviewed by Franco et al [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bull spermatozoa, a study by Hur et al [68] reported that the protein of KCK4 localizes to the equatorial region of acrosome reacted sperm, and that inhibitor of the K 2P channels reduces not only fertilization but also development of bovine and mouse embryos in vitro. Interestingly, a DMR was located in the CTCF gene, which has been associated with spermatogenesis and male fertility [70, 71]. The CTCF gene plays a critical role in genome-wide gene regulation and has roles in epigenetic reprogramming, gametogenesis and embryo development and is also associated with fertility, as reviewed by Franco et al [70].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a DMR was located in the CTCF gene, which has been associated with spermatogenesis and male fertility [70, 71]. The CTCF gene plays a critical role in genome-wide gene regulation and has roles in epigenetic reprogramming, gametogenesis and embryo development and is also associated with fertility, as reviewed by Franco et al [70]. Indeed, a study by Hernandez-Hernandez et al [71] reported that mice with a conditional knock-out of the CTCF gene had smaller testis and spermatogenesis was impacted as several males were infertile.…”
Section: Discussionmentioning
confidence: 99%
“…These regions can encompass regulatory loci (e.g., enhancers and silencers/regulators) that are outside of promoters and gene bodies. They can act independently or in concert with proximal regulatory regions, and alter chromatin organization and thus expression (44,45). Using putative regulators identified from the FANTOM5 cap analysis of gene expression atlas, changes in the methylation status of regulators (42,46) between conception types was examined.…”
Section: Characteristics Of Differential Methylationmentioning
confidence: 99%
“…The methyl-CpG-binding protein family is considered the "readers of the epigenome" as these proteins recruit histone deacetylases and methylases as well as chromatin remodelers to methylated DNA segments associated with gene repression (Du et al, 2015). On the other hand, CTCF serves as a protein insulator to regulate intra-and inter-chromosomal configuration, DNA methylation as well as global chromatin organization and remodeling, contributing to the repression or activation of gene transcription (Franco et al, 2014;Haggarty, 2015).…”
Section: B Epigenetics and Human Diseasesmentioning
confidence: 99%